EFFECT OF HUMIC ACID, SEAWEED EXTRACTS AND ORGANIC FERTILIZER ON YIELD QUALITY OF BROCCOLI (Brassica oleracea) GROWN UNDER PLASTIC HOUSE - Ismael, Salih Farhan; Sarhan, Taha Zubeir (Science Journal of University of Zakho, 2025)
The research was carried out at the protected cultivation department in Zakho Technical Institute, Dohuk Polytechnic University, Kurdistan region of Iraq during growing season 2021-2022 aiming to investigate the effect of foliar application of humic acid and seaweed extract each at concentrations (0, 2, and 4) ml.L-1 and soil addition of organic fertilizer (animal manure) at three rates (0, 5, and 10) ton.ha-1 on yield quality of broccoli cultivar (Agassirz) grown in plastic house. The experiment was designed following a randomized complete block design (RCBD) with three replicates. The earned results showed that the humic acid, seaweed extract, and organic manure, either individually or interacted, caused a prominent amelioration in the head qualitative traits such as Chlorophyll content (SPAD), Total soluble solids (TSS %), Ascorbic acid (%), Vitamin B1 (µg. L-1), and Total carotene (vitamin A) mg. L-1 as compared with control. The ever-highest values were obtainable from the treatment: humic acid at (4) ml. L-1 + seaweed extract at (4) ml. L-1 + organic fertilizer at (10) tons. donum-1, which was superior to control and other treatments. The foliar application of humic acid and seaweed extract at a concentration of 4 ml. L-1 and soil addition of organic manure at level 10 tons. donum-1 is recommended for the organic production of broccoli cultivar (Agassirz).